Pelaksanaan Model Manajemen Partisipatif Dalam Pendidikan : Studi Kasus di Sekolah Menengah Pertama - Fathoni, Muhammad; Fatimah, Tria Siti; Cahyani, Samantha; Syah, Umniyyatul Auliya (IAIN Parepare, 2023)
The dynamics of implementing educational activities in Indonesia need to be improved. For this improvement, the participation of school community members is necessary so that all existing dynamics can be handled as effectively as possible. Therefore, management and its functions need to be applied in the participation of school community members and the public so that educational activity programs can run effectively and efficiently. This research aims to determine the implementation of participatory management at SMP Pelita Harapan. The researcher used a qualitative method in the data collection process, which includes observation, interviews, and the distribution or filling out of questionnaires with the target being school community members. The observation was conducted to review the process of implementing participatory management directly at SMP Pelita Harapan. Interviews were conducted with members of the SMP Pelita Harapan community to find out their responses regarding the implementation of participatory management at the school. The distribution of questionnaires to school community members, containing statements with response classifications such as strongly agree, agree, disagree, and strongly disagree, was done to obtain more detailed information or data regarding the implementation of participatory management at SMP Pelita Harapan. The results of the research show that the implementation of participatory management at SMP Pelita Harapan is quite good, but there is a need for improvement in some aspects that hinder the implementation of participatory management, such as a lack of teachers, inadequate facilities and infrastructure, and others. It is the responsibility of the school principal to address these dynamics by involving the school community so that participatory management at SMP Pelita Harapan can be carried out effectively.